PENGARUH PENGENDALIAN INTERN TERHADAP KINERJA KARYAWAN STUDI PADA PT BANK PANIN TBK CABANG KENDARI - Taradipa, Putri Seyla (JURNAL AKUNTANSI, 2017)
Â Thisstudyaimedto examinetheeffect oftheinternalcontrol on employeeperformance(StudyonPT.Bank PaninTbkcabangKendari). Primary datainthis study were obtained fromthe perception of all employees atPaninBank cabangKendari.Perceptions ofrespondentsmeasured by questionnaireanswers usingordinalmeasurementwitha5-point Likertscale. Thestatisticalmethod usedtotest eachhypothesisissimpleregression analysis.Theresults showedthattheinternal control significantinfluenceon employeeperformance.CoefficientAdjustedR Squareresultsofthe regressionof0.824 or 82.4%.Theremaining17.6%is explainedbyother variablesnotexamined.Thisshowsthat thebettertheinternalcontrol implementedwill improve employeeperformancebecomes better.Â Keywords:Internal control andemployeeperformance.ABSTRACTÂ Thisstudyaimedto examinetheeffect oftheinternalcontrol on employeeperformance(StudyonPT.Bank PaninTbkcabangKendari). Primary datainthis study were obtained fromthe perception of all employees atPaninBank cabangKendari.Perceptions ofrespondentsmeasured by questionnaireanswers usingordinalmeasurementwitha5-point Likertscale. Thestatisticalmethod usedtotest eachhypothesisissimpleregression analysis.Theresults showedthattheinternal control significantinfluenceon employeeperformance.CoefficientAdjustedR Squareresultsofthe regressionof0.824 or 82.4%.Theremaining17.6%is explainedbyother variablesnotexamined.Thisshowsthat thebettertheinternalcontrol implementedwill improve employeeperformancebecomes better.